PKM MAHASISWA INDO GLOBAL MANDIRI PADA E-COMMERCE MARKETPLACE ERA PANDEMI COVID MENINGKAT TAJAM - Ayu Safitri , Della; Fitriani, Desy; Hertati, Lesi; Terttiaavini; Heryati, Agustina; Asmawati (Transpublika Publisher, 2021)
During the ongoing COVID-19 pandemic, the Indonesian government implemented Large-Scale Social Restrictions (PSBB) to curb the spread of the coronavirus. These restrictions have limited community mobility, resulting in the need for adaptation to new circumstances. The shift from in-person shopping to online platforms has become essential for fulfilling basic needs. E-commerce, the electronic buying and selling of goods, has emerged as a crucial solution. This study aims to examine whether there are differences in visits to e-commerce websites in Indonesia in light of these behavioral changes. A quantitative approach is employed, utilizing data on website visits during the COVID-19 pandemic and distributing questionnaires. The findings demonstrate that the pandemic has indeed impacted the number of visits to e-commerce websites. The increase in website visits has led to a surge in online financial transactions, a greater demand for expedited delivery services due to the high volume of products to be shipped, an increase in the requirement for packaging materials, and a higher demand for labor in product packaging services.